Disaster governance and prospects of inter-regional partnership in the Asia-Pacific - Cook, Alistair David Blair (2021)
The Southwest Pacific is considered one of the most vulnerable regions in the world to natural hazards. Five of the Pacific Island States (PIS) rank among the top 20 most-at risk countries in the World Risk Index, with Vanuatu and Tonga ranking first and second respectively. The Southwest Pacific neighbours Southeast Asia and both regions are exposed to a variety of natural hazards, resulting in significant damage and loss of lives annually. Similar exposure to climate-induced hazards raises the potential to create a coalition of affected states from the Asia-Pacific to share knowledge of disaster governance in areas where niche capabilities have been developed and shape the global debate on the effects of natural hazards and climate-induced disasters. This article argues that inter-regional partnership on disaster governance is the next step in the Asia-Pacific to respond to a collective action problem affecting two sub-regions - Southeast Asia and the Southwest Pacific. Through the conduct of desk research and interviews, this article first presents findings and observations on the disaster governance landscape and future developments in the Pacific. It then discusses disaster management frameworks and initiatives that ASEAN has institutionalised, and how work in the two sub-regions can complement one another and provide a platform to help shape the global agenda on disaster governance and climate change.